2018
DOI: 10.1002/jmor.20791
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure and distribution of sensilla on the maxillary and labial palps ofChlorophorus caragana(Coleoptera: Cerambycidae)

Abstract: Chlorophorus caragana is a species of long-horned beetle that damages Caragana davazamcii Sancz. (Fabales: Papilionaceae) bushes in desert areas in China. The beetles cause substantial damage to local forestry plantations and the environment. Sensilla on the maxillary and labial palps of coleopterans a allow the insects to recognize their host plants. We used scanning and transmission electron microscopy to study the ultrastructure, distribution, and abundance of various sensilla on the maxillary and labial pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 66 publications
(90 reference statements)
1
4
0
Order By: Relevance
“…In addition, the oral appendages of adult G. cantor (labial palpus and mandibular palpus) are mainly involved in host selection, oviposition, mating and other behaviors (Zhang et al, 2018;Hall et al, 2019). In the gross morphology of the labial palpus and mandibular palpus, we also found that there was obvious dimorphism, which is consistent with Aphis gossypii Glover and Diaphorina citri Kuwayama (Ettay et al,2001;Bento et al,2017), especially in terms of length.…”
Section: Discussionsupporting
confidence: 84%
“…In addition, the oral appendages of adult G. cantor (labial palpus and mandibular palpus) are mainly involved in host selection, oviposition, mating and other behaviors (Zhang et al, 2018;Hall et al, 2019). In the gross morphology of the labial palpus and mandibular palpus, we also found that there was obvious dimorphism, which is consistent with Aphis gossypii Glover and Diaphorina citri Kuwayama (Ettay et al,2001;Bento et al,2017), especially in terms of length.…”
Section: Discussionsupporting
confidence: 84%
“…Here, we hypothesize that the sensilla on the antennae and ovipositor play an important role in selecting and locating the ultimate host. It is well known that the ultrastructural study of insects sensilla could provide evidence for the function of sensory organs (Altner & Prillinger, 1980; Zhang et al, 2018). To date, many studies have shown that the antennae and ovipositors of Hymenopteran insects can sense host information through search and contact efforts, and those behaviors rely on antennal and ovipositor sensilla, which are especially important for those species of parasitoids that depend on chemical cues to locate their hosts (Ahmed, Zhang, He, Bai, & Wang, 2013; Amornsak, Cribb, & Gordh, 1998; Bleeker, Smid, van Aelst, van Loon, & Vet, 2004; Cönsoli et al, 1999; Das et al, 2011; Dweck, 2009; Dweck & Gadallah, 2008; Gao, Luo, & Hammond, 2007; Li, Lu, Liu, Zhang, & Zhou, 2011; Nacro & Nénon, 2009; Norton & Vinson, 1974; Onagbola & Fadamiro, 2008; Onagbola, Boina, Hermann, & Stelinski, 2009; Rocha, Moreira, & Redaelli, 2007; Roux, Baaren, Gers, Arvanitakis, & Legal, 2005; Shah, 2012; van Baaren, Boivin, Le Lannic, & Nénon, 1999; van Lenteren et al, 2007; Wang, Yang, & Gould, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the mandibular and labial palpi of the adult G. cantor play a major role in host choice, oviposition, mating, and other activities (Hall et al, 2019; Zhang et al, 2018). We also observed apparent dimorphism in the gross morphology of the labial and mandibular palpi, which is similar with Aphis gossypii Glover and Diaphorina citri Kuwayama (Bento et al, 2017; Ettay & Moshe, 2001).…”
Section: Discussionmentioning
confidence: 99%